UJI MANN WHITNEY DALAM KOMPARASI HASIL BIMBINGAN PRAKTIK KEWIRAUSAHAAN MAHASISWA ANTARA DOSEN LAKI-LAKI DAN PEREMPUAN PADA FAKULTAS EKONOMI UNIVERSITAS PAMULANG - Ali Mubarok; Sahroni Sahroni; Sunanto Sunanto (Procuratio : Jurnal Ilmiah Manajemen, 2021)
The purpose of this research is to determine there is or no difference in the results of entrepreneurial practice of students between male and female lecturers at the faculty of Economics University of Pamulang. This type of research is quantitative comparatively with hypothesis testing. The population in this research is a lecturer in the management and accounting faculty of the Economics of Pamulang University which is recorded as a lecturer in practice guidance in the semester of even 2017/2018 in the Institute of Business Incubation and Entrepreneurship (Pinbik) University of Pamulang using saturated samples amounting to 66 classes of guidance. The data analysis method is assisted with SPSS program and for hypothesis testing with the Mann Whitney U test. The results of the study concluded there was no significant difference between the guidance of the entrepreneurial practice of students between male and female professors at the economics faculty of Pamulang University. It is derived from the Mann Whitney test with the acquisition of the ASYMP value. Sig. (2 tailed) 0.470 > 0.05 meaning Ho is accepted. Penelitian ini bertujuan untuk mengetahui ada atau tidak ada perbedaan hasil bimbingan praktik kewirausahaan mahasiswa antara dosen laki-laki dan perempuan pada Fakultas Ekonomi Universitas pamulang. Jenis Penelitian ini adalah komparatif kuantitatif dengan pengujian hipotesis. Populasi dalam penelitian ini adalah dosen Prodi Manajemen dan Akuntansi Fakultas Ekonomi Universitas Pamulang yang yang tercatat sebagai dosen pembimbing praktik pada semester Genap 2017/2018 dalam Lembaga Pusat Inkubasi Bisnis dan Kewirausahaan (Pinbik) Universitas Pamulang dengan menggunakan sampel jenuh berjumlah 66 kelas bimbingan praktik. Metode analisis data dibantu dengan program SPSS dan untuk pengujian hipotesis dengan Mann Whitney U test. Hasil penelitian menyimpulkan tidak terdapat perbedaan yang signifikan antara hasil bimbingan praktik kewirausahaan mahasiswa antara dosen Laki-laki dan Perempuan pada Fakultas Ekonomi Universitas Pamulang. Hal ini didapat dari Uji Mann Whitney dengan perolehan nilai Asymp. Sig. (2 tailed) 0,470 > 0,05 yang berarti Ho diterima.